The growth of short fatigue cracks in titanium and aluminium alloys - Bolingbroke, Richard Kendall (1988)
An investigation has been made of the growth of An investigation has been made of the growth of short fatigue cracks in aluminium and titanium alloys, with special emphasis on the effects of microstructure.